The digital divide: A review and future research agenda - Lythreatis, Sophie; Singh, Sanjay Kumar; El-Kassar, Abdul-Nasser (Technological forecasting & social change, 2022)
•Digital divide is a grand societal challenge.•The pandemic has exacerbated the digital divide.•Factors affecting the divide can be classified into 9 main categories.•New forms of the digital divide are emerging.•Digital divide should be problematized more. This article provides a systematic review of the digital divide, a phenomenon which refers to disparities in Information and Communications Technology access, usage, and outcomes. It uniquely identifies the factors affecting the digital divide that have emerged in recent years (2017–2021) as well as investigate if there are new forms or levels of the divide that have surfaced in recent literature. The findings, based on 50 included studies, show that the factors affecting the digital divide can be classified into three different segments and nine main categories: sociodemographic, socioeconomic, personal elements, social support, type of technology, digital training, rights, infrastructure, and large-scale events. Out of all factors, education has been linked to the digital divide the most. The majority of recent literature have studied Level 2 of the divide. Also, only one article in the sample has considered the digital divide at the firm level. Findings also show that a new form, type-of-internet access, and two potential new levels of the digital divide, algorithmic awareness and data inequalities, have been identified in the contemporary literature. The results contribute to the understanding and development of the different perspectives of the digital divide concept. They also contribute to the stream of literature on the determinants of the divide and to the social inequalities and digital inclusion literature. This review can be seen as a guide for managers to realize and understand the forms that the divide can take and to delve into their organizational capabilities on the digitalization front and evaluate where further development is needed within their organizations to help diminish the divide.